Narrativas Dominantes en Torno A La Adaptación Familiar en Un Grupo de Mujeres Excombatientes del Conflicto Armado en Colombia (2016)
This research describes narratives of ex-combatants women of the illegal armed group in Colombia, where the familiar experiences are identified, before, during and after, that were present in his environment. Approached from a structural and evolutionary systematic approach with qualitative methodology, whereby the stories that were obtained from female ex-combatants through the biographical conversational interview technique were handled. It was used the inductive categorization for its analysis, according to the categories that were raised. The analysis allowed identify that for this group of women to rebuild their family ties, gives them a significant force that helps them in their process of adaptation adequately, allowing them to evolve.